Pengaruh Persepsi Siswa Terhadap Pembelajaran Matematika Daring Dan Luring Pada Hasil Belajar Matematika Siswa - Niawati, Zulin; Shodikin, Ali (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2022)
This study aims to determine the effect of student perceptions on online and offline learning on student learning outcomes. The research hypotheses tested included: 1) students' perceptions of online and offline learning. The influence of students 'perceptions of online and offline Mathematics learning on students' mathematics learning outcomes. The research was conducted by using the experimental method. The sample size was 4 grade 2 students at SMK NU 1 Simo Karanggeneng Lamongan. The research instrument used was a test of mathematics learning outcomes in the form of descriptions with an option of 4 questions whose validity has been tested, student response questionnaires to online and offline learning, and interviews. Data analysis used a Likert scale table. The results of the study obtained the following conclusions: (1) Students' perceptions of online and offline mathematics learning are different. (2) There is an effect of students 'perceptions of online and offline mathematics learning on students' mathematics learning outcomes. This is due to many factors such as the unpreparedness of students and teachers in carrying out online learning, the material taught online cannot be understood by students.